Linear and nonlinear viscoelastic properties of segmented silicone-urea copolymers: Influence of the hard segment structure. (9th January 2020) - Falco, Guillaume; Simonin, Léo; Pensec, Sandrine; Dalmas, Florent; Chenal, Jean-Marc; Bouteiller, Laurent; Chazeau, Laurent
Abstract: The linear and non-linear viscoelastic behaviors of 5 segmented silicone copolymers - with low fraction of 1, 6-hexamethylene diisocyanate (HDI), 4, 4′-methylenebis (cyclohexyl isocyanate) (HMDI), 1, 3-bis(1-isocyanato-1-methylethyl)benzene (TMXDI), 2, 4-tolylene diisocyanate (TDI) or isophorone diisocyanate (IPDI) as hard segments (HS) - are compared, in relation with their microstructure. When the HS are non-symmetrical, the materials nanostructuration is weak and has a limited impact on the mechanical response: two mechanical relaxations occur after the α relaxation of the polydimethylsiloxane (PDMS), the first related to the "unfreezing" of the HS-HS bonds, and the second one to the sticky reptation of the polymer chains. Conversely, when the HS are symmetrical, their self-organization is favored and the long range ordering of the HS is possible. The materials are then semi-crystalline like, with a low crystallinity (due to the low weight percentage of HS) and their flow, possible above their melting temperature ( T m ), depends also on the HS dynamics, which is the most rapid for HDI. Graphical abstract: Image 1 Highlights: With low wt% of non-symmetric HS, nanostructuration is weak. Two mechanical relaxations occur after the α one. The first is related to "unfreezing" of the HS-HS bonds, the second to sticky reptation. The non linear behavior can be deduced from the linear one.